Supporting mathematics and science teachers in implementing intercultural learning - Sorge, Stefan; Doorman, Michiel; Maass, Katja; Straser, Oliver; Hesse, Alice; Jonker, Vincent; Wijers, Monica (ZDM, 2023)
Our current multicultural societies require that education addresses diversity and promotes cultural awareness and intercultural learning. Mathematics and science education can also contribute to this aspect of citizenship education and create a culture of belonging for all students. Professional development that integrates intercultural learning with educational practices is still uncommon in the field of science and mathematics teacher preparation and support. This study explores the possibilities to support science and mathematics teachers in implementing intercultural learning through a professional development course. The course was developed in a European setting, based on a theoretical analysis, and tried out with 319 teachers from six participating countries. The impact of the course on teachers’ take up of intercultural learning was measured with a pre-post questionnaire. We found that the course strengthened teachers’ self-efficacy beliefs and extended their teaching practices with opportunities created by cultural diversity among their students or in their subjects. In addition to that, teachers’ self-efficacy beliefs and the perceived cultural diversity in class appeared to be influencing factors for teachers’ practices. Based on our findings we recommend that the combination of intercultural learning with educational practices of mathematics and science might be a suitable gateway to provide new intercultural learning opportunities for students.